2010
DOI: 10.1029/2009ja015107
|View full text |Cite
|
Sign up to set email alerts
|

Wave and particle characteristics of earthward electron injections associated with dipolarization fronts

Abstract: [1] A comprehensive examination of particle and wave data from multiple Thermal Emission Imaging System (THEMIS) satellites has been made of an electron injection structure in the magnetotail as it propagated earthward from −20 R E to −11 R E on 27 February 2009. The electron injection, which was closely associated with a dipolarization front and bursty bulk flows, occurred within a thin plasma boundary layer and had both perpendicular and parallel energization, with very little energy dispersion. The thin pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
235
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(245 citation statements)
references
References 49 publications
(67 reference statements)
8
235
1
1
Order By: Relevance
“…[63] Deng et al [2010] reported novel observations of double layers and solitary pulses in earthward electron injection events in the magnetotail from THEMIS observation. These events are associated with dipolarization of the geomagnetic field lines accompanied by bursty bulk flows of plasma.…”
Section: Electron Holes and Double Layers In Electron Injection Eventmentioning
confidence: 99%
“…[63] Deng et al [2010] reported novel observations of double layers and solitary pulses in earthward electron injection events in the magnetotail from THEMIS observation. These events are associated with dipolarization of the geomagnetic field lines accompanied by bursty bulk flows of plasma.…”
Section: Electron Holes and Double Layers In Electron Injection Eventmentioning
confidence: 99%
“…A number of case studies [Le Contel et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Huang et al, 2012] reported observations of whistlers in relation to DFs. In particular, they found whistlers in the magnetic flux pileup region (FPR), where the electron distribution has a perpendicular anisotropy, which is large enough to drive whistlers via the whistler anisotropy instability [Le Contel et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…DFs are identified by a sharp increase of B z GSM and are associated with electron and ion acceleration [Asano et al, 2010;Zhou et al, 2010;Fu et al, 2011] as well as various wave activities, e.g., electron holes, whistler, lower hybrid, and electron cyclotron waves [Le Contel et al, 2009;Sergeev et al, 2009;Zhou et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Hwang et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Malykhin et al: Contrasting dynamics of electrons and protons 1992; Nakamura et al, 2002;Runov et al, 2009). DFs are associated with electron and ion acceleration (e.g., Apatenkov et al, 2007;Asano et al, 2010;Zhou et al, 2010;Fu et al, 2011;Birn et al, 2011;Grigorenko et al, 2017) as well as with various wave activities, e.g., whistler emissions, lower hybrid and electron cyclotron waves (e.g., Le Contel et al, 2009;Zhou et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Hwang et al, 2011;Vilberg et al, 2014;Grigorenko et al, 2016). BBFs with embedded DFs transport energy and mass from a remote tail source to the near-Earth plasma sheet (PS), where the high-speed flows are slowed down and diverted (e.g., Sergeev et al, 2009;Ge et al, 2011 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The last may lead to additional energization and/or particles scattering and losses via processes of wave-particle interactions (e.g., Le Contel et al, 2009;Zhou et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Panov et al, 2013;Fu et al, 2014;Vilberg et al, 2014;Zhang and Angelopoulos, 2014;Grigorenko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%